Characterization of dusts from secondary copper production - Orac, Dusan; Laubertova, Martina; Piroskova, Jana; Klein, Dusan; Bures, Radovan; Klimko, Jakub (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Various types of waste, including dusts, are produced in the pyrometallurgical production of copper from secondary raw materials. According to the European Waste Catalogue and Hazardous Waste List, dusts from secondary copper production are classified as hazardous waste. In secondary copper production 3.87 million tons of copper were produced worldwide in 2017. The dusts are produced in the following thermal operations: reduction of the melt in the shaft furnace (shaft furnace dust), converting (converter dust) and pyrometallurgical refining (refining dust). These dusts contain significant amounts of heavy metals (Zn, Pb and Sn) in oxidic form. The dusts are considered as secondary raw materials, and it is necessary to look for ways of extracting these heavy metals. The aim of this work was to characterize the individual types of dust and determine their quantitative and qualitative composition. The content of heavy metals in copper shaft furnace dust is (52.16% Zn, 19.33% Pb), in copper converter dust (32.40% Zn, 14.46% Pb), and in refining dust (32.99% Zn).